The Australian idea of a university - Davis, Glyn (Melbourne University Press, 2017)
Universities, like other industries, are challenged by disruptive market forces. Today there are nearly forty public universities in Australia. Some predict that by 2070 there may be only ten institutions left globally to deliver higher education. Relentless inventiveness and entrepreneurial agendas promise students a world of unbounded study options. In this powerful meditation on the need for institutional diversity, Glyn Davis argues that experimentation, innovation and resilience are the only way the public university will endure.